ANALISIS TUNDAAN KENDARAAN PADA U-TURN DI RUAS JALAN JOHAN IDRUS – JALAN M. SOHOR – JALAN SUTOYO PONTIANAK - Kashogi, Tessar Abdillah; Kadarini, Siti Nurlaily (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
The problem of congestion in Pontianak is quite complex. Congestion that occurred causing the length of travel time in traveling from origin to destination. One of the factors influencing traffic jam in Pontianak City is the number of vehicles that do turning (U-Turn), thus inhibiting the smooth flow of traffic. This study aims to determine the amount of delay due to vehicles that make U-turn in several streets in Pontianak City, such as Jalan Johan Idrus, Jalan M. Sohor, and Jalan Letjen Sutoyo.The regression analysis method is used to generate a numerical form and to see how two variables (simple regression analysis) or more than two variables (multiple regression analysis) are interrelated. The survey was conducted to observe the normal travel time of U-turn vehicles, the length of vehicle movement due to queue of vehicles, and the length of queue of vehicles due to U-Turn. Meanwhile, the geometric data of each road are also measured, such as the width of the lane, the width of the road, the median opening, the median width that is considered to influence the research results.The analysis results show that the duration of movement and delay of four or more wheeled vehicles that do the reverse is influenced by 2 variables, ie the opposite direction volume and the median width. The best model for a single U-Turn is: long movement Y = 12.050 + 0.003 X2 - 3.145 X5; delay Y = 5.499 + 0.003 X2 - 3.145 X5. The best model for Double U-Turn is: long movement: Y = 16.921 + 0.0009 X2 - 2.756X5; delay Y = 10.370 + 0.0009 X2 - 2,756 X5. The recommendations that can be given in this research are the geometric changes of the road, in this case the widening of the lane and the median to shorten the length of the delay of the U-turn vehicle.